ANALISIS KEBIJAKAN KAMPUS MENGAJAR PERINTIS DALAM MENINGKATKAN KETERAMPILAN MENGAJAR CALON GURU SEKOLAH DASAR UNIVERSITAS NUSA CENDANA - Fembriani, Fembriani; Koroh, Taty R.; Nawa, Netty E. A. (Journal of Character and ELementary Education, 2023)
The independent learning campus policy is designed to help students explore their creativity and excel in various fields. The Elementary School Teacher Education Study Program as one of the implementers of the independent campus, especially the “kampus mengajar” program, makes a real, full contribution. Starting from the pioneering “kampus mengajar”, there were 59 students. The topic of this research is the implementation of the independent learning policy on the teaching campus at PGSD, Nusa Cendana University. The purpose of this study was to see the achievements of PGSD at Nusa Cendana University in terms of teaching campus policies. Researchers used a qualitative descriptive method. Procedures for collecting information through interviews, observation, and questionnaires. Data analysis Milles and Huberman methods include summarization, analysis, and inference. The results showed that students were skilled in the aspect of explaining skills very well, in the skill aspect of carrying out learning variations, guiding discussions, and teaching in small groups and individually the skills of students were identified as good. Therefore, students need knowledge, understanding, and application of basic teaching skills in order to carry out their duties properly at school. This can be owned by students by maximizing their potential and the provision provided by the Ministry of Education and Culture before assignments in the field. The role of Field Supervisors in this case is also needed to monitor and evaluate students during the program. Synergy between students and Field Supervisors is needed in terms of improving the basic teaching skills possessed by students participating in “kampus mengajar”.